Downregulated lncRNA HOXA11-AS Affects Trophoblast Cell Proliferation and Migration by Regulating RND3 and HOXA7 Expression in PE - Yetao Xu; Dan Wu; Jie Liu; Shiyun Huang; Qing Zuo; Xi Xia; Ying Jiang; Sailan Wang; Yanzi Chen; Tianjun Wang; Lizhou Sun (Elsevier, 2018)
The long noncoding RNA HOXA11-AS displays abnormal expression in numerous human diseases. However, its function and biological mechanisms remain unclear in preeclampsia (PE). In this study, we report that HOXA11-AS is significantly downregulated in preeclamptic placental tissues and could contribute to the occurrence and development of PE. Silencing of HOXA11-AS expression could significantly suppress trophoblast cell growth and migration, whereas HOXA11-AS overexpression facilitated cell growth in the HTR-8/SVneo, JEG3, and JAR cell lines. RNA-seq analysis also indicated that HOXA11-AS silencing preferentially regulated numerous genes associated with cell proliferation and cell migration. Mechanistic analyses showed that HOXA11-AS could recruit Ezh2 and Lsd1 protein and regulate RND3 mRNA expression in the nucleus. In the cytoplasm, HOXA11-AS modulates HOXA7 expression by sponged miR-15b-5p, affecting trophoblast cell proliferation. Together, these data confirm that aberrant expression of HOXA11-AS is involved in the occurrence and development of PE and may act as a prospective diagnosis and therapeutic target in PE. Keywords: HOXA11-AS, preeclampsia, proliferation, RND3, HOXA7